Generation and Testing of Fluorescent Adaptable Simple Theranostic (FAST) Proteins - Andrew Flies; Jocelyn Darby; Peter Murphy; Terry Pinfold; Amanda Patchett; Patrick Lennard (Bio-Protocol, 2020)
This protocol provides a step-by-step method to create recombinant fluorescent fusion proteins that can be secreted from mammalian cell lines. This builds on many other recombinant protein and fluorescent protein techniques, but is among the first to harness fluorescent fusion proteins secreted directly into cell culture supernatant. This opens new possibilities that are not achievable with proteins produced in bacteria or yeast, such as direct use of the fluorescent protein-secreting cells in live co-culture assays. The Fluorescent Adaptable Simple Theranostic (FAST) protein system includes a histidine purification tag and a tobacco etch virus (TEV) cleavage site, allowing the purification tag and fluorescent protein to be removed for therapeutic use. This protocol is split into five parts: (A) In silico characterization of the gene-of-interest (GOI) and protein-of-interest (POI); (B) design of the expression vector; (C) assembly of the expression vector; (D) transfection of a eukaryotic cell line with the expression vector; (E) testing of the recombinant protein. This extensive protocol can be completed with only polymerase chain reaction (PCR) and cell culture training. Additionally, each part of the protocol can be used independently.